STRUCTURAL MODELING OF PHENYLALANINE AMMONIA-LYASES AND RELATED MIO-CONTAINING ENZYMES – AN INSIGHT INTO THERMOSTABILITY AND IONIC INTERACTIONS - BÁNÓCZI, Gergely; SZABÓ, Csongor; BATA, Zsófia; FILIP, Alina; HORNYÁNSZKY, Gábor; POPPE, László (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Biocatalysis and bioinformatics are powerful tools to analyze and enhance the properties of biocatalysts for industrial technologies. In this work, the three-dimensional structures of various phenylalanine ammonia-lyases and other 5-methylene-3,5-dihydro-4H-imidazol-4-one (MIO) dependent enzymes were investigated, analyzed, and constructed. The three- dimensional structures of MIO-containing aromatic ammonia-lyases and 2,3-aminomutases from the PDB database were analyzed. In several instances, the structural deficiencies and inactive conformations were modified to approach the active states. The checked / modified PDB structures of the MIO-enzymes served as templates for the large-scale homology modeling for phenylalanine ammonia-lyase (PAL) sequences with unknown structure. Multiple settings were tested in the modeling workflow to result in structures with intact active center, good overall protein quality and reasonable number of salt bridges. The experimental temperature optima of the investigated PALs were correlated with two common factors of thermal stability: salt bridge and disulfide bridge numbers. Our study indicate i) a moderate correlation between salt bridge numbers and temperature optima, ii) and negligible effects of disulfide bridges. The two examples which do not correlate with the others, indicate the presence of other important factors contributing to thermal stability of the MIO-enzymes. The modified PDB structures can serve further molecular modeling projects such as functional studies with a QM/MM approach.